MaRISA-AOCode: uma abordagem genérica para geração de código orientado a aspectos - Guimarães, Everton Tavares (2010)
Currently there are several aspect-oriented approaches that are related to different stages of software development process. These approaches often lack integration with each other and their models and artifacts are not aligned in a coherent process. The integration of Aspect-Oriented Software development (AOSD) and Model-Driven Development (MDD) enables automatic propagation of models from one phase to another, avoiding loss of important information and decisions established in each. This paper presents a model driven approach, called Marisa-AOCode, which supports the processing of detailed design artifacts to code in different Aspect-Oriented Programming languages. The approach proposed by Maris- AOCode defines transformation rules between aSideML, a modeling language for aspectoriented detailed design, and Metaspin, a generic metamodel for aspect-oriented programming languages. The instantiation of the generic metamodel (Metaspin) provided by the approach of Maris-AOCode is illustrated by the transformation of Metaspin for two languages: AspectLua and CaesarJ. We illustrate the approach with a case study based on the Health Watcher System